THE IMPACT OF EMPOWERMENT OF THE HEGINES AND HALAL PRODUCTION PROCESS IN JAYA ABADI MICRO BUSINESS GUNUNGANYAR TAMBAK SURABAYA ON THE IMPROVEMENT OF THE LOCAL ECONOMY - Dr. H. Zakariya Zakariya ,MS, MM; Drs. Ec. Kunto Inggit Gunawan, MM; Drs. Ec. Mataji Mataji, MM (JPM17: Jurnal Pengabdian Masyarakat, 2021)
Surabaya is the second Metropolitan city after Jakarta, of course economic development must not only focus on investment-intensive sectors, but also must encourage the SME and Micro Business sectors because it has significance in employment. Strengthening the local economy becomes important to encourage economic justice as an implication of the growth of SMEs and Micro Enterprises. For this reason, the purpose of this research is to look at the impact of empowering the hegines and halal production processes of the Surabaya is the second Metropolitan city after Jakarta, of course economic development must not only focus on investment-intensive sectors, but also must encourage the SME and Micro Business sectors because it has significance in employment. Strengthening the local economy becomes important to encourage economic justice as an implication of the growth of SMEs and Micro Enterprises. For this reason, the purpose of this research is to look at the impact of empowering the hegines and halal production processes of the Micro Jaya Abadi Gununganyar Tambak Surabaya business on improving the local economy. The method used is descriptive qualitative by comparing before and after production processes before and after from the aspects of hegines and halal while also comparing the potential level of absorption of local labor with before and after approaches as well. The results showed that there were significant differences after assistance was made in understanding the clean and halal production process, where the values are as follows, before with a value of 53 and after the mentoring was carried out at 67.5.While the employement rate increased 50% Keywords: Empowerment – Production of Hegines and Halal – Local Economy